Modification of Steepest Descent Method for Solving Unconstrained Optimization - Zubai'dah Binti Zainal Abidin (Universiti Malaysia Terengganu, 2023)
The Classical steepest descent (SD) method is known as one of the earliest and the best method to minimize a function. Even though the convergence rate is quite slow, but its simplicity has made it one of the easiest methods to be used and applied especially in the form of computer codes.